The effect of the Internet in learning a language (Journal of Universal Science Research, 2023)
This article deals with the importance and opportunities of the Internet in a language learning process.It is given that the utilization of  the Internet,including networking sites,online platforms for communicating with foreigners provides learners with a good source of manual materials,video lessons and good language learning environment.The benefits and aspects of the information-communicative technologies in educational system is indetail shown.There is no doubt that learning  a language with  using such kind of technologies is hopefully best way.